Manis Belum Tentu Aman: Edukasi Pemanis Buatan pada Minuman Kemasan bagi Siswa SMP IT Citra Ummat Kota Tidore Kepulauan (Lembaga Pengembangan Kinerja Dosen, 2026)
The consumption of sugar-sweetened packaged beverages among adolescents continues to increase along with changes in lifestyle and dietary patterns. Limited knowledge regarding artificial sweeteners, recommended intake limits, and the potential health risks of excessive consumption may contribute to unhealthy beverage choices. This community service program aimed to improve students' knowledge of artificial sweeteners in packaged beverages through health education at SMP IT Citra Ummat, Tidore Islands City. The program involved 67 seventh- and eighth-grade students and was implemented through interactive lectures, discussions, question-and-answer sessions, supported by PowerPoint presentations, educational banners, and leaflets. Knowledge was assessed using pre-test and post-test questionnaires, and the data were analyzed using the Wilcoxon Signed Rank Test. The results showed that 33 students (49.3%) experienced increased knowledge scores, 23 students (34.3%) showed no change, and 11 students (16.4%) had decreased scores. Statistical analysis demonstrated a significant difference between pre-test and post-test scores (Z = -3.500; p = 0.000), indicating that the educational intervention effectively improved students' knowledge regarding artificial sweeteners in packaged beverages. The program also enhanced students' awareness of the importance of reading nutrition facts and ingredient labels before purchasing packaged beverages. Health education can therefore serve as an effective promotive strategy to improve food safety literacy among adolescents.